Survivability of 1-chloronapthalene during simulated early diagenesis – Implications for chlorinated hydrocarbon detection on Mars - Royle,SH; Tan,J; Kounaves,SP; Sephton,M (Journal of Geophysical Research: Planets, 2018)
All missions to Mars which have attempted to detect organic molecules have detected simple chlorohydrocarbons, the source of which has yet to be firmly established. This study assessed the likelihood of these chlorinated molecules being indigenous to the sedimentary units in which they were detected or if they were chlorinated during analysis. The survivability of 1-chloronapthalene was examined via hydrous pyrolysis experiments and its de-chlorination kinetics were determined. The results of these experiments were used to model the survivability of this simple chlorohydrocarbon under Mars-relevant diagenetic conditions using the Sheepbed mudstone unit as a case study. It was found that 1-chloronapthalene was rapidly dechlorinated under Noachian conditions and thus the detected Martian chlorohydrocarbons are unlikely to be ancient and probably formed within the rover’s sample handling chain during analysis.